Impending threats to the plants with medicinal value in the Eastern Himalayas Region: An analysis on the alternatives to its non-availability - Dr. Suman Ray; Mahesh Kumar Saini (Elsevier, 2022)
Background: The extreme human interference today has resulted in a threat to tens of thousands of species with extinction. Herbal medicines are becoming popular and this has enhanced the research towards ethnobotanical and ethnomedicinal investigation on herbal products. Consequently, medicinal plants are now under great pressure due to its increased demand. Hypothesis/Purpose: Fast population growth and economic development have imposed unprecedented levels of extinction risk and yet these threats are inevitable.  One of these risks is threat to medicinal plants and its medicinal value. The purpose of the study was to explore impending threats to the medicinal value of plants due to loss of biodiversity in the Eastern Himalayas Region and the alternatives to its non-availability. Study Design: Secondary data was used to create a dataset of 108 rare, endangered, threatened, extinct, and vulnerable plants from India's Himalayan northeast region that have medicinal properties useful for the treatment of various diseases. Methods: Cluster analysis of these selected dataset of 108 medicinal plants was done using Free Tree software version 0.9.1.50 and Fig Tree version 1.2.2. This analysis produced a Jaccard Neighbor-joining dendrogram and the mathematical consensus tree was established after 1000 bootstrap replicates were performed. Results: Analysis of the relativeness of the Rare, Endangered, Threatened, Extinct, Vulnerable plants on the basis of medicinal properties provides a key to alternative to non-availability of herbs. The data analysis shows how important it is to preserve much of Earth's remaining plant biodiversity. Conclusion: The paper indicates an urgent action to protect these threatened medicinal plants species and prevent the loss of its medicinal value.